Hubungan antara Senam Zilgrei dengan Lama Inpartu Kala II pada Primigravida - Agnis Sabat Kristiana; Riskhiana Rahayu (Journal of Ners and Midwifery, 2016)
The second stage of labor is one of the stages of labor that starts from the complete opening (10 cm) until the baby is born, and at primigravidas lasts 1 hour. Prolonged labor amounted to 5% of all causes of maternal death. One of method to restrain the prolonged labor is to do zilgrei gymnastics. This study purposed to find the correlation of gymnastics zilgrei and long inpartu of second stage in primigravida. The design of this study was observational analytic with cross sectional approach. The population in this study was inpartu primigravida maternity who do zilgrei gymnastics in January 2014â€“March 2015 in BPS Ny â€œSâ€ Tunggulwulung village Malang with 40 respondents and the sample of 40 respondents using total sampling techniques. The instrument used a data collection sheet from the book documentation of labor BPS Ny â€œSâ€.The results showed Spearman correlation test at 5% error level and p value = 0.0001 <0.05. This means that Ho was rejected and Ha accepted and there was a significant correlation between zilgrei gymnastics with inpartu on second stage. The suggestion of this research was for health employee to socialize the implementation of zilgrei gymnastics as well as the benefits for the labor, so that the second stage of labor does not take a long time.